Lao People's Democratic Republic : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Lao People's Democratic Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the 2007 Article IV Consultation on the Lao People's Democratic Republic (PDR) explains economic performance. Growth is robust and increasingly reliant on large export-oriented mining and hydropower projects. The economic outlook is promising, but the outcome clearly depends on the government's policy response to the emerging resource bonanza. The current fiscal regimes for the resource sector have several sound features, but some improvements are needed to align them to best international practices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet